Neighbourhood greenness moderates the association between physical activity and geriatric-relevant health outcomes: an analysis of the CLSA - Andrew Putman; Irmina Klicnik; Shilpa Dogra (BMC Geriatrics, 2023)
Abstract Background The purpose of this analysis was to evaluate the relationship between baseline physical activity levels of older adults and geriatric-relevant health outcomes at 3-year follow-up, and to determine whether baseline neighbourhood characteristics alter this association. Methods Data from the Canadian Longitudinal Study on Aging (CLSA) were used to assess geriatric-relevant outcomes of physical impairment, medication use, severity of daily pain, and depressive symptoms. Data from the Canadian Active Living Environments (Can-ALE) and the Normalized Difference Vegetative Index (NDVI) were used to determine neighbourhood walkability and greenness, respectively. The analytic sample included adults who were 65 years or older at baseline $$(n=\text{16,735}, age=73± 5.6, 50% female)$$ . Adjusted odds ratios and 95% confidence intervals for the base relationships were calculated using proportional odds logistic regression (physical impairment, pain, medication use), and linear regression (depressive symptoms). Moderation effects of environmental factors were assessed using greenness and walkability. Results The base relationships showed protective associations between each additional hour per week of total physical activity and physical impairment $$\left(OR=0.95, 95%CI=\text{0.94,0.96}; p<.001\right),$$ daily pain severity $$\left(OR=0.98, 95%CI=0.98, 0.99; p<.001\right),$$ medication use $$(OR=0.98, 95%CI= 0.97, 0.99; p< .001)$$ , and depressive symptoms $$(OR=0.95, 95%CI=\text{0.94,0.96}; p<.001)$$ . Additive moderation effects were seen when greenness was added to physical impairment $$(β =0.022, p=.04)$$ , daily pain severity $$(β =0.019, p<.01)$$ , and depressive symptoms $$(β =0.032, p=.01)$$ but no moderation was seen with walkability. Sex differences were observed. For example, greenness moderation was found in severity of daily pain in males but not in females. Conclusion Future research investigating geriatric-relevant health outcomes and physical activity should consider neighbourhood greenness as a potential moderator.